Success of extracorporeal shock wave lithotripsy based on CT texture analysis. Issue 11 (15th September 2021) - Erkoc, Mustafa; Bozkurt, Muammer; Besiroglu, Huseyin; Canat, Lutfi; Atalay, Hasan A.
Abstract: Objective: The aims of the study were to evaluate whether computerised tomography texture analysis (CTTA) based on non‐contrast computed tomography (NCCT) has predictive value for the success of extracorporeal‐shockwave lithotripsy (ESWL) in upper urinary tract stones (UUTS). Methods: This study included 156 of 356 patients undergoing ESWL for UUTS sized 0.5‐2 cm from 2015 to 2019. Patients with congenital kidney anomalies, radiolucent stones, multiple stones, treated for upper urinary tract stones previously and lower pole stones were excluded from study. The number of ESWL sessions of the patients was as follows: 78 (50%) patients had 1 session, 30 (19.2%) patients had 2 sessions and 48 (30.8%) patients had >2 sessions. First‐ and second‐order CTTA properties of patients' UUTS were evaluated using texture analysis software (LIFEx Software). Other clinical features such as Hounsfield Unit (HU), initial stone size, body‐mass index (BMI) and skin to stone distance (SSD) was recorded. The patients were divided into two groups according to ESWL success. Cases with residual stones larger than 4 mm were considered failed cases. Results: BMI, the standard deviation of HU, SSD, skewness, kurtosis, entropy and all second‐order statistics were found to be statistically different between the two groups except for correlation ( P  < .05). Multivariate analysis showed longer SSD and four new parameters of CTTA (kurtosis, entropy, dissimilarity and energy by the distribution of pixel grey levels in the UUTS) to be significant predictors for unsuccessful ESWL outcomes. SSD and second‐order CTTA properties (dissimilarity and energy) had an area under ROC curve of 0.802, 0.850 and 0.824 at a 95% confidence interval. ESWL success rate in all patients was 76.9%. Conclusion: CTTA can help select patients who will undergo ESWL for upper urinary tract stones. Thus, we can reduce treatment costs and ESWL complications by preventing unnecessary ESWL applications.